Peningkatan Pengetahuan Ibu tentang Stunting di Puskesmas Simpang Tiga Kelurahan Bukit Raya - Fitra Mayenti; Ika Permanasari; Fiki Cahaya Putra Indra; Agus Salim; Ika Yoga Kumara; Yoda Triadi; Ripandra Duper; Arya Ramadia (Jurnal Abdimas Kesehatan (JAK), 2026)
Stunting is a chronic nutritional problem that has a significant impact on children's physical growth and cognitive development. One of the main determinants of stunting is the low level of maternal knowledge regarding balanced nutrition, parenting practices, and the early detection of growth disorders. This community service program was designed to improve mothers' knowledge of child nutrition through interactive health education. The community service activity was conducted on April 29, 2025, involving 20 participants. The program included a pre-test to assess mothers' baseline knowledge, followed by health education on stunting, and concluded with a post-test to evaluate changes in knowledge after the intervention. The results of this community service activity showed an improvement in mothers' knowledge about stunting. The number of mothers with good knowledge increased from 6 participants (30%) before the intervention to 20 participants (100%) after the intervention. These findings indicate that the health education provided was effective in enhancing mothers' understanding of stunting and the importance of ensuring balanced nutrition for children